(untitled) (International Journal of Food and Nutritional Sciences, 2022)
65 percent of India’s population still depends on agriculture. Agriculture is moving through a transition. After independence, the biggest challenge faced by the government was to satisfy the hunger of the growing population. Therefore, various activities were implemented to increase productivity. The agricultural extension system was made more efficient. Research institutes started emphasizing on high yielding varieties and production technology. The objective of increasing production began to bear fruit. The green revolution contributed a lot to that. Although this achievement is something to be proud of, the fact cannot be denied that the small and poor farmers have not been able to make the expected progress. Considering the country’s need of the time and the urgency of immediate productivity increase, most of the activities fell into the form of ’top-down’ technology flow, so local people’s participation in various phases remained nominal. Due to the efforts of the extension system and research institutes, India has not only become self-sufficient in food grain production, but now the country has also started exporting agricultural products; But in this situation, it is also necessary to consider the small and marginal farmers who are more than 80 percent in our country. For this, extension systems have been ordered to change their working methods. The spread of technology based on local needs and problems, people’s participation, cropping methods, joint ventures is the highway of sustainable agriculture and more than one way of sustainable income is being built in rural development through an integrated farming system. This will benefit the farmers. Also, it is very important to adopt integrated farming system for sustainable development so that agriculture can be developed well and farmers can become prosperous.